The Immune System - Parham, Peter (New York: W.W. Norton & Company, 2021)
A clear, concise, and contemporary presentation of immunological concepts. This text emphasizes the human immune system and presents concepts with a balanced level of detail to describe how the immune system works. Written for undergraduate, medical, veterinary, dental, and pharmacy students, it makes generous use of medical examples to illustrate points. This classroom-proven textbook offers clear writing, full-color illustrations, and section and chapter summaries that make the content accessible and easily understandable to students
Keywords: Immune system; Immunopathology